Sabang and ikn synergy: reconfiguration of the eastern maritime region for a blue economy in state law - Mauldya Nailya, Cut; Suryaningsi, Suryaningsi; Wingkolatin, Wingkolatin; Marwiah, Marwiah (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study aims to analyze the strengthening of Indonesia's west-east maritime axis through the synergy between the Sabang Strategic Area and the Nusantara Capital City (IKN) in supporting the development of the blue economy. As an archipelagic country, Indonesia faces the challenge of inter-island connectivity as well as a great opportunity to strengthen maritime sovereignty and national economic equity. The position of Sabang as the western gateway and the IKN in East Kalimantan as the center of the new government in the middle of the archipelago provides strategic potential in forming an integrative and sustainable maritime axis. The study method uses a state law approach by examining decentralization policies, institutional strengthening, and optimization of maritime law and regional autonomy. The analysis shows that the Sabang-IKN synergy is able to strengthen the state's role in integrating regions, improving sea connectivity, and supporting the development of a fair and sustainable blue economy. This synergy also emphasizes Indonesia's vision as the world's maritime axis through the management of marine resources that is in favor of the welfare of the people. In conclusion, the strategic collaboration between Sabang and IKN is an important instrument to realize maritime sovereignty, equitable development, and regional justice in accordance with the mandate of Article 33 of the 1945 Constitution. Policies that prioritize strengthening national connectivity, protecting maritime law, and regional empowerment are key in the implementation of strengthening the west-east maritime axis as a pillar of the constitution-based blue economy